(untitled) (Actualizaciones en Sida e Infectología, 2023)
Introduction: The incidence of carbapenem-resistant Enterobacterales (CRE) rose in the last decade, and especially during the COVID-19 pandemic. Objective: To identify the antimicrobial resistance profile, as well as the frequency and type of carbapenems that were present in CRE isolations in a tertiary care hospital. Materials and methods: Epidemiological, observational and retrospective study. It included CRE isolated in clinical samples during 2021 in a tertiary care hospital in Argentina. Incidences (isolations/patients-day), confidence intervals of 95% (CI 95%) and statistical comparisons were made with OpenEpi. Results: 348 CRE were isolated (11.9 isolations/1,000 patients-day, IC95% 10.7-13.2). Incidence correlated to COVID-19 cases (rho=0.874, p<0.001). Most isolations were from the Intensive Care Unit (76.4%) and the from respiratory samples (27.6%, n=96) and blood cultures (24.4%, n=92). The main isolated CRE was Klebsiella pneumoniae (71.4%, n=260), with a general carbapenem resistance of 53.4%. KPC was the main resistance mechanism (61.2%). Two double carbapenemase-producing Enterobacterales were isolated. Klebsiella pneumoniae presented a higher overall resistance rate to non-betalactam antibiotics (60.6% vs 38.5%, p<0.001). Among CRE, a higher colistin resistance rate was found in KPC isolations (44.6% vs 23.9%, p=0.001) and lower resistance to amikacin (23.9% vs 72.6%, p<0.001). Conclusion: The difficulty in the selection of antibiotic regimens for CRE forces the treating physicians to put emphasis on the knowledge of resistance mechanisms to optimize them.